ANALYSIS OF THE USAGE OF HANYU JIAOCHENG TEXTBOOK IN THE EIGHTH GRADE AT KALAM KUDUS JUNIOR HIGH SCHOOL, BANDUNG - Kezia Forienka Carrin Natasha; Selvia Selvia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
Mandarin is the second international language that is widely studied in schools. Mandarin is unique in its tone, Han characters, and how it is pronounced. In learning a language, textbooks are needed that are appropriate to the level of the learner. Many schools include Mandarin as both intra-curricular and extra-curricular activities, one of which is Kalam Kudus Junior High School, Bandung, with the aim of learning to target students to have four basic language skills namely reading, listening, writing, speaking with balanced competence. Of course, they also expect their students to be able to recognize Han's characters. This study focuses on the analysis of the use of the Hanyu Jiaocheng Book in Grade 8 Kalam Kudus Junior High School, Bandung. This study uses qualitative research methods with data collection techniques in the form of interviews, questionnaires, and direct observation. From the research that the writers conducted, it was found that the Hanyu Jiaocheng textbooks used in Kalam Kudus Junior High School, Bandung, Bandung were still not relevant to the goals set by the school because the textbooks did not contain listening exercises, besides teachers and students found ithem difficult because the textbooks are in English as the descriptions. The writers hopes that this research can provide input to schools to review the Chinese textbooks used to improve the learning process of Mandarin in the future.